2001
DOI: 10.1093/nar/29.24.4994
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Sp3 is regulated by acetylation

Abstract: Sp3 is a ubiquitous transcription factor closely related to Sp1. Previous analyses showed that, unlike Sp1, Sp3 fails to activate transcription in certain promoter settings. This is due to the presence of an inhibitory domain located between the second glutamine-rich activation domain and the DNA-binding domain. To further analyze the transcriptional properties of Sp3, we have expressed and purified recombinant Sp3 and Sp1 as epitope-tagged proteins from stable transfected insect cells. We found that Sp3 does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 32 publications
2
117
0
Order By: Relevance
“…In support of this assumption, treatment of Hep3B cells and SL2 cells with HDAC inhibitor TSA caused the phosphorylation of Sp1, leading to the activation of its transcriptional activity (Choi et al, 2002). We also do not exclude the possibility that the transcriptional activation of p21 WAF1/Cip1 by apicidin might be mediated by hyperacetylation of Sp1 and/or Sp3, because Sp3 can be acetylated in vivo (Braun et al, 2001). Also, other nonhistone proteins such as the p53 or E2F transcription factor are thought to be regulated by reversible acetylation (Martinez-Balbas et al, 2000;Prives and Manley, 2001).…”
Section: Discussionmentioning
confidence: 92%
“…In support of this assumption, treatment of Hep3B cells and SL2 cells with HDAC inhibitor TSA caused the phosphorylation of Sp1, leading to the activation of its transcriptional activity (Choi et al, 2002). We also do not exclude the possibility that the transcriptional activation of p21 WAF1/Cip1 by apicidin might be mediated by hyperacetylation of Sp1 and/or Sp3, because Sp3 can be acetylated in vivo (Braun et al, 2001). Also, other nonhistone proteins such as the p53 or E2F transcription factor are thought to be regulated by reversible acetylation (Martinez-Balbas et al, 2000;Prives and Manley, 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Acetylation of Sp1 likely occurs at lysine residues within the DNA-binding domain (31), whereas the location of acetylation of Sp3 has not yet been precisely determined. Previously, we have shown that mutation of the SUMO lysine 551 impaired acetylation of Sp3 in vivo (32). This finding suggested originally that the same lysine residue that is a target for SUMOylation is also a target for acetylation.…”
Section: An Upstream Open Reading Frame Is Involved In Regulating Sp3mentioning
confidence: 87%
“…Proteins that can be either sumoylated or ubiquitylated include I B␣ in the NF-B transcription pathway (Desterro et al 1998), pathogenic Huntington's disease protein Huntingtin (Steffan et al 2004), and the DNA polymerase auxiliary factor, PCNA (Hoege et al 2002). Further, sumoylation-deacetylation interplay has been suggested for the transcription factor Sp3 (Braun et al 2001;Ross et al 2002).…”
Section: Discussionmentioning
confidence: 99%